Biomedical Engineering and Design Handbook, Volume 1 - Kutz, Myer (McGraw-Hill Education, 2009)
A state-of-the-art guide to the fundamentals of biomedical engineering, covering the biomechanics of the human body, biomaterials, and bioelectronics. The two-volume Biomedical Engineering and Design Handbook offers you unsurpassed coverage of the entire biomedical engineering field, including the fundamental concepts, design processes and procedures, and applications. This landmark work contains contributions on a wide range of engineering and design problems from over 40 leading experts at universities and medical centers around the globe. Volume 1 focuses on the basics of biomedical engineering, taking you step-by-step through biomedical systems analysis, biomechanics of the human body, diagnostic instrumentation, design of medical devices, biomaterials, and bioelectronics. Filled with over 500 detailed illustrations, this superb volume will give you the foundation of information needed to understand the development of new devices, techniques, and treatments.